Penetrative and non-penetrative interaction between Laboulbeniales fungi and their arthropod hosts - Ana Sofia P. S. Reboleira (Nature Portfolio, 2021)
Abstract Laboulbeniales are a highly specialized group of fungi living only on arthropods. They have high host specificity and spend their entire life-cycle on an arthropod host. Taxonomic characters of Laboulbeniales are based on the architecture of the cells of the parenchymal thallus, i.e. the visible part of the fungus outside the host. The extent of the fungus spreading inside the host—the haustorium—remains largely unknown. The attachment to the arthropod host is fundamental to understand the fungus-animal interaction, but how this truly occurs is unclear. Recent evidences question the strictly parasitic life-style of Laboulbeniales. We used micro-computed tomography (µCT) and 3D reconstructions to visualize, for the first time, the complete structure of Laboulbeniales species in situ on their hosts. We compared the haustoriate species, Arthrorhynchus nycteribiae on an insect host to the non-haustoriate species, Rickia gigas on a millipede host. Our results confirm that some Laboulbeniales species are ectoparasitic and have a haustorial structure that penetrates the host’s cuticle, while others are ectobionts and are only firmly attached to the host’s cuticle without penetrating it. The presence and the morphology of the haustorium are important traits for Laboulbeniales evolution, and key factors for future understanding of host dependence and specificity.